The role of athlete leadership quality in the characteristics of team resilience in elite soccer teams: a cross-sectional and longitudinal mediation of team identification - López-Gajardo, M. A.; González-Ponce, I.; García-Calvo, T.; Enrich-Alturo, E.; Leo, F. M. (Journal of Clinical Sport Psychology, 2024)
We present two studies examining the relationship between athlete leadership quality and team resilience and explored the mediating effect of team identification. In Study 1, 194 soccer players (Mage = 18.50, SD = 4.49) from eight national teams participated. Structural equation modeling showed cross-sectionally that the four types of athlete leadership qualities were positively related to the characteristics of resilience and negatively to vulnerability under pressure. Team identification was shown to be a mediator of these relationships. Study 2, with four different time-points, involved 208 young soccer players (Mage = 16.05, SD = 3.39) from two professional clubs (i.e., La Liga). Cross-lagged panel models revealed that task leadership quality (Times 1-2) was positively related to the characteristics of resilience (Times 3-4) and negatively to vulnerability under pressure (Times 3-4). However, team identification did not mediate these relationships. Therefore, practitioners should consider the perceptions of leader quality to achieve benefits during competition.